Quality Improvement of Honey Product Using Quality Function Deployment (QFD) Method - Dian, Tiara Maha; Sucipto, Sucipto (Department of Agro-industrial Technology, University of Brawijaya, 2021)
AbstractThis study aims to determine the priority of honey product attributes and determine the proposed improvement of honey products. The research was conducted in a company engaged in honey bee cultivation. 4-phase QFD is used in this study. Phase 1 is for product quality improvement planning, phase 2 is for product improvement design, phase 3 is for improvement process planning, and phase 4 is for process control improvements. The results showed that the attributes that needed to be improved were price, packaging color, product color, and ease of opening the product. The ease of opening the product did not affect the increase in sales of Super Honey so that the improvement of these attributes was not prioritized. The priority of the technical response in the planning and design of product improvement was the improvement of packaging color and product color improvement. The priority of the technical response in planning and controlling the improvement process was the procurement of 600 ml volume bottles with a new type of cap. This priority considered that the technical response was related to improving the packaging color and improving the performance of the price attribute. The procurement of the 600 ml bottle with the new type of cap also involved parties outside the company, thus requiring a longer production time.Keywords: consumer needs, honey, quality improvement AbstrakPenelitian ini bertujuan untuk menentukan prioritas atribut produk madu dan menentukan usulan perbaikan produk madu. Penelitian dilakukan di perusahaan yang bergerak di bidang budidaya lebah madu. QFD 4 fase digunakan pada penelitian ini. Fase 1 dilakukan untuk perencanaan perbaikan kualitas produk, fase 2 dilakukan untuk desain perbaikan produk, fase 3 dilakukan untuk perencanaan perbaikan proses, dan fase 4 dilakuk untuk perbaikan kontrol proses. Hasil penelitian menunjukkan bahwa atribut yang perlu diperbaiki adalah harga, warna kemasan, warna produk, dan kemudahan membuka produk. Kemudahan membuka produk tidak mempengaruhi peningkatan penjualan madu Super sehingga perbaikan atribut tersebut tidak diprioritaskan. Prioritas respon teknis pada perencanaan dan perancangan perbaikan produk adalah perbaikan warna kemasan dan perbaikan warna produk. Prioritas respon teknis pada perencanaan dan pengendalian proses perbaikan adalah pengadaan botol volume 600 ml dengan jenis tutup baru. Hal ini disebabkan respon teknis tersebut terkait dengan perbaikan warna kemasan dan peningkatan kinerja atribut harga. Pengadaan botol volume 600 ml dengan jenis tutup baru tersebut juga melibatkan pihak di luar perusahaan dan membutuhkan waktu produksi yang lebih lama daripada label kemasan.Kata Kunci: madu, perbaikan kualitas, suara konsumen